2000
DOI: 10.1128/iai.68.8.4430-4440.2000
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Proinflammatory Cytokines from Human Respiratory Epithelial Cells after Stimulation by NontypeableHaemophilus influenzae

Abstract: Nontypeable Haemophilus influenzae (NTHi) causes repeated respiratory infections in patients with chronic lung diseases. These infections are characterized by a brisk inflammatory response which results in the accumulation of polymorphonucleated cells in the lungs and is dependent on the expression and secretion of proinflammatory cytokines. We hypothesize that multiple NTHi molecules, including lipooligosaccharide (LOS), mediate cellular interactions with respiratory epithelial cells, leading to the productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 70 publications
4
41
1
Order By: Relevance
“…Diverse microbial pathogens stimulate airway epithelial cells, leading to activation of the transcriptional activator NF-B and production of proinflammatory cytokines, such as IL-6 and IL-8 (5,15,20,28,30). In this study, we observed that CS inhibited IL-8 production brought about by NT H. influenzae and S. aureus in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 54%
“…Diverse microbial pathogens stimulate airway epithelial cells, leading to activation of the transcriptional activator NF-B and production of proinflammatory cytokines, such as IL-6 and IL-8 (5,15,20,28,30). In this study, we observed that CS inhibited IL-8 production brought about by NT H. influenzae and S. aureus in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 54%
“…In our model, we did detect proinflammatory cytokines at early time points postinfection, suggesting that nonmacrophage lung cells are capable of compensating for the absence of AMs. We suggest that epithelial cells are responsible for the observed early cytokine production and for triggering neutrophil recruitment, as epithelial cells can produce IL-8 in response to influenza virus and IL-6, IL-1␣, IL-1␤, and TNF-␣ in response to Haemophilus influenzae (51,52). Ongoing studies are focused on elucidating the effects of S. marcescens on epithelial cell cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…A further possibility is that release of Hap facilitates the degradation of target host proteins such as tissue components or immune system effectors. Interestingly, the first experiments to find a Hapimmune system interaction have shown that Hap does not induce proinflammatory cytokines from human respiratory epithelial cells but that immunization with the purified protein does protect mice against nasopharyngeal colonization with wild-type organisms (68,86).…”
Section: H Influenzae Adhesion and Penetration Protein (Hap)mentioning
confidence: 99%
“…68,2004 TYPE V SECRETION 695 signal sequence which targets proteins for secretion to the Sec inner membrane secretion pathway (for in-depth reviews, see references 115; 245; and 509). The Sec machinery is composed of an ATPase, SecA, several integral inner membrane proteins (SecD, SecE, SecF, SecG, and SecY, and a signal peptidase (116,338).…”
Section: Two-step Type II Protein Secretionmentioning
confidence: 99%